Relationship between children’s and parents’ blood pressure - Desy Aswira Nasution; Rusdidjas Rusdidjas; Supriatmo Supriatmo; Rafita Ramayati; Oke Rina Ramayani; Rosmayanti Siregar (Paediatrica Indonesiana, 2014)
Background A family history of hypertension is a risk factor forhypertension in children. Past studies have reported a significantrelationship between elevated blood pressure in children andhypertensive parents.Objective To assess for an association between blood pressure inchildren and that of their parents.Methods A cross-sectional study was conducted in 90 childrenaged 6-18 years in Baringin Village, Panyabungan, from May toJune 2010. Subjects were collected by consecutive sampling.Classification of hypertension was based on Fourth Task ForceGuidelines by measuring blood pressure, height, and weight. Weused Student's T-test to analyze numerical data. Simple linearregression was used to investigate the relationship between bloodpressures of children and their parents.Results Of the 90 participants recruited, 24 boys and 17 girlshad hypertensive parents. The mean systolic (SBP) , diastolic(DBP) and arterial blood pressure (MABP) were significantlyhigher in children with hyperten sive parents than in childrenwith normotensive parents [ (SBP 116. 7 (SD 7 .07) vs. 87 .1 (SD13.57) mmHg; P=0.0001), (DBP 77.8 (SD 8.33) vs. 51.8 (SD11.70) mmHg; P=0.0001), (MABP 90.7 (SD 7.41) vs . 63 .6(12.10) mmHg; P=0.000 1] . There was a significant relationshipbetween elevated SBP in boys and their fathers, as indicated bythe correlation coefficient (r =0.806; P=0.0001).Conclusion The blood pressure is significantly higher in childrenwith hypertensive parents than in those with normotensiveparents. There is a correlation between SBP in boys and that oftheir fathers.